Extraction of endometrial polyps and type 0 submucosal fibroids under ultrasonographic guidance when hysteroscopy is not available (Annals of Medical Research, 2021)
Aim: Endometrial polyp (EP) and type 0-uterine leiomyoma (T0SLM) in the uterus are common pathologies encountered in daily practice. Hysteroscopic resection is the gold standard for removal of these lesions. However, hysteroscopy might not be available in low-source settings. Management of intracavitary lesions by using an ultrasonography-guided approach is presented in this study.Material and Methods: Between March 2016 and June 2018, 14 out of 67 patients diagnosed with EP and T0SML applied to a gynecology department of a tertiary center when hysteroscopic approach was not available and refused to be referred to another city for hysteroscopic approach. All the patients had a thorough ultrasonographic evaluation and saline infusion sonography prior to the surgery. Surgical intervention of the patients was performed under sedation anesthesia. Using a ring forceps, EPs or T0SML were held under ultrasonographic guidance and then removed completely using rotation and traction.Results: The age range and the diameter of the lesions ranged between 35-71 years and 21-61 mm respectively. The mean duration of the surgery was 8.5 ± 1.9 minutes. Eight patients had EP while six had T0SML. In the postoperative 4th month follow-up examination via ultrasonographic investigation, no residual lesion was observed in any of the patients.Conclusion: Although hysteroscopy is the gold standard in the treatment of EP/T0SML, its availability is sometimes limited. Moreover, the cost of hysteroscopy is high in comparison to the conventional methods. Requirement of surgical experience and the necessity of morcellation for the removal of large lesions make hysteroscopy more complicated. Removal of precisely selected large T0SML and EP is effective and cost-effective.
Keywords: Endometrial polyp; ring forceps; submucosal fibroid; ultrasonography